Hubungan Pengetahuan, Sikap Dan Motivasi Dengan Perilaku Mobilisasi Dini Pada Ibu Post Seksio Sesarea Di RSIA ‘Aisyiyah Samarinda - Hasanah, Rahmatin (PT WIM Solusi Prima, 2024)
Background: The importance of early mobilization in post-cesarean section mothers, the role of an officer is very necessary to provide explanation and motivation, accompany and guide post-cesarean section mothers to mobilize as early as possible. A preliminary study conducted by researchers on five post-section mothers found the phenomenon of three post-cesarean section mothers claiming to be still afraid to do early mobilization for various reasons, including because they still feel pain and still feel weak to move. Excessive fear of postpartum mothers causes them to experience dependence on health workers in the implementation of early mobilization Objective: Analyze the relationship of knowledge, attitudes and motivations towards early mobilization behavior in postpartum mothers with SC at RSIA 'Aisyiyah Samarinda. Methodology: This study uses correlational picture method and cross sectional research design, the sample technique with purposive sampling so that 75 respondents are obtained and uses multiple linear regression tests. Results: After analysis, the results were 0.000 smaller than 0.05 α which means that there is a significant relationship between knowledge, attitudes and motivation of mothers towards early mobilization in post-cesarean section mothers at RSIA 'Aisyiyah Samarinda. Benefits: The results of this study are to add insight for postpartum mothers with SC so as not to have concerns about early mobilization which is useful to do after undergoing a cesarean section. Tujuan studi: menganalisis dihubungan pengetahuan, sikap dan motivasi terhadap perilaku dimobilisasinya secara dini pada ibu yang pasca melahirkan dengan SC di RSIA ’Aisyiyah Samarinda. Metodologi: Penelitian ini menggunakan metode gambaran korelasional dan desainnya penelitian cross sectional, diteknik sampelnnya dengan purposive sampling sehingga diperoleh 75 responden dan menggunakan uji diregresi linier berganda. Hasil: Setelah dianalisis didapatkannya hasil 0,000 lebih kecil dari 0,05 α yang artinya adanya hubungan yang signifikan antara pengetahuan, sikap dan motivasi ibu terhadap mobilisasi dini di pada ibu post seksio sesarea di RSIA ‘Aisyiyah Samarinda. Manfaat: Hasil dipenelitian ini agar menambah wawasan bagi ibu pasca persalinan dengan SC supaya tidak memiliki kekhawatiran mengenai mobilisasi dini yang berguna untuk dilakukan setelah menjalani operasi Caesar.